Low Temperature Synthesis of Superparamagnetic Iron Oxide (Fe3O4) Nanoparticles and Their ROS Mediated Inhibition of Biofilm Formed by Food-Associated Bacteria - Al-Shabib, Nasser A.; Husain, Fohad Mabood; Ahmed, Faheem; Khan, Rais Ahmad; Khan, Mohammad Shavez; Ansari, Firoz Ahmad; Alam, Mohammad Zubair; Ahmed, Mohammed Asif; Khan, Mohd Shahnawaz; Baig, Mohammad Hassan; Khan, Javed Masood; Shahzad, Syed Ali; et al. (Frontiers in Microbiology, 2018)
In the present study, a facile environmentally friendly approach was described to prepare monodisperse iron oxide (Fe3O4) nanoparticles (IONPs) by low temperature solution route. The synthesized nanoparticles were characterized using x-ray diffraction spectroscopy (XRD), Raman spectroscopy, field emission scanning electron microscopy (FESEM) measurements, Fourier-Transform Infrared Spectroscopy (FTIR), and Thermogravimetric analysis (TGA) analyses. XRD patterns revealed high crystalline quality of the nanoparticles. SEM micrographs showed the monodispersed IONPs with size ranging from 6 to 9 nm. Synthesized nanoparticles demonstrated MICs of 32, 64, and 128 μg/ml against Gram negative bacteria i.e., Serratia marcescens, Escherichia coli, and Pseudomonas aeruginosa, respectively, and 32 μg/ml against Gram positive bacteria Listeria monocytogenes. IOPNs at its respective sub-MICs demonstrated significant reduction of alginate and exopolysaccharide production and subsequently demonstrated broad-spectrum inhibition of biofilm ranging from 16 to 88% in the test bacteria. Biofilm reduction was also examined using SEM and Confocal Laser Scanning Microscopy (CLSM). Interaction of IONPs with bacterial cells generated ROS contributing to reduced biofilm formation. The present study for the first time report that these IONPs were effective in obliterating pre-formed biofilms. Thus, it is envisaged that these nanoparticles with broad-spectrum biofilm inhibitory property could be exploited in the food industry as well as in medical settings to curtail biofilm based infections and losses.